2015
DOI: 10.3758/s13428-015-0652-6
|View full text |Cite
|
Sign up to set email alerts
|

Normative study of theme identifiability: Instructions with and without explanation of the false memory effect

Abstract: False-memory illusions have been widely studied using the Deese/Roediger-McDermott paradigm (DRM). In this paradigm, words semantically related to a single nonpresented critical word are studied. In a later memory test, critical words are often falsely recalled and recognized. The present normative study was conducted to measure the theme identifiability of 60 associative word lists in Spanish that include six words (e.g., stove, coat, blanket, scarf, chill, and bonnet) that are simultaneously associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…The DRM paradigm has been extensively used to study the mechanisms underlying false memories by manipulating variables such as backward and forward associative strength (e.g., Brainerd and Wright, 2005;Arndt, 2012Arndt, , 2015Arndt, 2014, 2017), presentation rate (e.g., Seamon et al, 1998;Smith and Kimball, 2012;Sadler et al, 2018), number of words associated to the critical lure (e.g., Arndt, 2010;Flegal and Reuter-Lorenz, 2014), presentation modality (e.g., Mao et al, 2010;Boldini et al, 2013), retrieval time (e.g., Giammattei and Arndt, 2012;Carneiro et al, 2014), attentional demands (e.g., Pérez-Mata et al, 2002;Otgaar et al, 2012), distinctive encoding (e.g., Huff et al, 2015Huff et al, , 2020, warning instructions (e.g., Watson et al, 2004;Carneiro and Fernandez, 2010;Coane et al, 2016), identifiability of the critical lure (e.g., Neuschatz et al, 2003;Carneiro et al, 2009;Beato and Cadavid, 2016), or emotional valence (e.g., Bookbinder and Brainerd, 2016;Hellenthal et al, 2019;Chang et al, 2020), among many others. All these experimental manipulations confirmed the robustness of this paradigm to produce false memories.…”
Section: False Memories: the Drm Paradigmmentioning
confidence: 99%
“…The DRM paradigm has been extensively used to study the mechanisms underlying false memories by manipulating variables such as backward and forward associative strength (e.g., Brainerd and Wright, 2005;Arndt, 2012Arndt, , 2015Arndt, 2014, 2017), presentation rate (e.g., Seamon et al, 1998;Smith and Kimball, 2012;Sadler et al, 2018), number of words associated to the critical lure (e.g., Arndt, 2010;Flegal and Reuter-Lorenz, 2014), presentation modality (e.g., Mao et al, 2010;Boldini et al, 2013), retrieval time (e.g., Giammattei and Arndt, 2012;Carneiro et al, 2014), attentional demands (e.g., Pérez-Mata et al, 2002;Otgaar et al, 2012), distinctive encoding (e.g., Huff et al, 2015Huff et al, , 2020, warning instructions (e.g., Watson et al, 2004;Carneiro and Fernandez, 2010;Coane et al, 2016), identifiability of the critical lure (e.g., Neuschatz et al, 2003;Carneiro et al, 2009;Beato and Cadavid, 2016), or emotional valence (e.g., Bookbinder and Brainerd, 2016;Hellenthal et al, 2019;Chang et al, 2020), among many others. All these experimental manipulations confirmed the robustness of this paradigm to produce false memories.…”
Section: False Memories: the Drm Paradigmmentioning
confidence: 99%
“…We anticipated that such extremely low-BAS levels would make it difficult for participants to guess the critical lures. In fact, previous DRM studies with three-critical-lure lists have found a significant correlation between BAS and identifiability of the critical lures ( Beato and Cadavid, 2016 ). Therefore, we expected that the exceptionally low-BAS levels would also make it difficult to resort to recall-to-reject strategies guided by the logic of mutual exclusivity (e.g., identify-to-reject).…”
Section: Discussionmentioning
confidence: 90%
“…Instead, we think that if the DRM lists included multiples critical lures, a condition used in the present study, it would be more difficult to engage in an identify-to-reject strategy. Second, in previous studies, a positive correlation has been found between BAS and identifiability indexes of the critical lures (e.g., Beato and Cadavid, 2016). That is, critical lures were more easily identifiable as the theme in high-BAS lists than in low-BAS lists.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations